Multidimensional poverty and vulnerability in Sri Lanka, 2024-2025 - Stifel, David; Beleac, Traian; Headey, Derek D.; Munasinghe, Dilusha; Ranucci, Immacolata; Sabai, Moe; Stifel, Elizabeth; van Asselt, Joanna; Weerasinghe, Krishani; Hülsen, Vivien (International Food Policy Research Institute, 2025)
We assess multidimensional poverty and vulnerability in Sri Lanka using the BRIGHT Integrated Household Survey data for 2024-2025. Nearly one quarter of all Sri Lankans are multidimensionally poor, and nearly one half are multidimensionally vulnerable. The multidimensionally poor are deprived in 45% of the weighted poverty indicators, while the multidimensionally vulnerable are deprived in 37% of the weighted vulnerability indicators. Estate areas have the highest rates of multidimensional poverty (63%) and vulnerability (83%), but most of the multidimensionally poor (77%) and vulnerable (79%) live in rural areas because nearly 8 out of 10 Sri Lankans live there. Central province has the highest multidimensional poverty rate (38%), while Northern (75%), Eastern (65%), and Uva (60%) provinces have the highest multidimensional vulnerability rates. Western province has one of the lowest multidimensional poverty rates (17%) and the lowest multidimensional vulnerability rates (35%). The main sources of multidimensional poverty are health deprivations and standard of living (assets and basic services) deprivations. The main sources of multidimensional vulnerability are shocks, unproductive debt, poor health, and inadequate schooling.